Contributions for the analysis of an educational change project (Praxis Educativa, 2012)
The purpose of this paper is to present the broad outlines of the conceptual framework was built, in order to operate as a “device analyzer” (Lapassade, G., 1979, Fernandez, L., 1996, Souto, M. 1999)– article provides the field of institutional studies for the analysis and interpretation of the relevant information with reference to educational change project taken as a case study. It should be noted that this theoretical framework has been synthesized according to the length of the article, which is why we present the main concepts that shape and conceptualization considered essential for each one of them. Moreover, with regard to the literature, it must be said that, for the same reason, reference is made here to the texts which are referred to in this presentation. In the following pages provide news about the investigation carried out on the present case and the relevant conceptual framework.
Keywords: institution; organization; change; crisis; power-authority